If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A = (4x + 5)(7x + -2) Reorder the terms: A = (5 + 4x)(7x + -2) Reorder the terms: A = (5 + 4x)(-2 + 7x) Multiply (5 + 4x) * (-2 + 7x) A = (5(-2 + 7x) + 4x * (-2 + 7x)) A = ((-2 * 5 + 7x * 5) + 4x * (-2 + 7x)) A = ((-10 + 35x) + 4x * (-2 + 7x)) A = (-10 + 35x + (-2 * 4x + 7x * 4x)) A = (-10 + 35x + (-8x + 28x2)) Combine like terms: 35x + -8x = 27x A = (-10 + 27x + 28x2) Solving A = -10 + 27x + 28x2 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Simplifying A = -10 + 27x + 28x2
| -3x+14=3 | | 9(y+3)= | | 2y^2+5y^2-3y^2= | | -12-1y=-15 | | 7x-3x+x-4+5x= | | (6x^5w^2-2xw^6)-(2xw^2)= | | 5b-5-7b-3= | | 4x+24=9x+26 | | -6y-15-7y=-20 | | -6y-15=-20 | | 9t^2+9t-10=0 | | t-46=-30 | | -6y-12+5=-15 | | 9x+3x=y | | 2/5x-6=-16 | | A=(4x+7)(2x+2) | | A=(4x+7)(2x-2) | | y^2+15y-3=0 | | 5y+x+32=5x+y | | A=(4x+7)(2x*2) | | x+-2x=-2 | | 21x^5y-7x^4y^2= | | 12(v+2)-3v=3(3v+1)-8 | | 10x-1=3(3x+2)-5 | | 5x^3-7x^2+8x-7=0 | | A=(9x+5)(4x-7) | | 10y^5+5y= | | 4v+44=7v+5 | | 50-3=8x | | [4x+12]=16 | | -6m^2+8n^2-10n= | | 2x^2-54x=116 |